Pengaruh Model Self Regulated Learning Terhadap Peningkatan Hasil Belajar Pada Mata Pelajaran Pekerjaan Dasar Elektromekanik - Ashari, Rizki Wahyu; Sujito, Sujito; Pratiwi, Ratna (Jurnal Pendidikan Teknik Elektro, 2025)
This research aims to improve student learning outcomes in the Basic Electromechanical Work subject through the implementation of the Self-Regulated Learning (SRL) model. The study employed a Classroom Action Research (CAR) design conducted in two systematic cycles, involving students of class X TOI at SMKN 1 Singosari. Each cycle was implemented through stages of planning, action, observation, and reflection to ensure continuous improvement of the learning process. Data on student learning outcomes were collected using multiple instruments, including cognitive achievement tests to measure conceptual understanding, psychomotor observation sheets to assess practical skills, and affective observation sheets to evaluate attitudes, motivation, and learning responsibility. The results of the research demonstrate a significant improvement in student learning outcomes across all three domains—affective, psychomotor, and cognitive—after the implementation of the SRL model. Students showed increased learning independence, better engagement in learning activities, and higher responsibility for their own learning processes. These improvements suggest that the SRL model effectively encourages active learning and supports students in managing their learning strategies, goals, and self-evaluation. Based on these findings, it can be concluded that the Self-Regulated Learning model is effective in enhancing student learning outcomes. Therefore, the implementation of SRL is strongly recommended as an alternative learning strategy for both practical and theory-based subjects to foster more meaningful and sustainable learning experiences.